2023
DOI: 10.1038/s41598-023-33291-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary micro-fibrillated cellulose improves growth, reduces diarrhea, modulates gut microbiota, and increases butyrate production in post-weaning piglets

Abstract: Dietary fiber (DF) supplementation is one of the strategies to prevent on-farm infections; it has the capability to improve gut health and piglet performance. Among the beneficial DFs, micro-fibrillated cellulose (MFC) is a new-generation plant-derived innovative feed ingredient; MFC, originating from sugar-beet pulp, has a hyper-branched structure with the ability to form shear-thinning hydrogel and has a high water-binding capacity. We aimed to determine the effects of MFC supplementation on piglets' perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…However, butyric acid is easily oxidized and denatured, producing a pungent odor. A trace amount of butyric acid was produced after fermentation in this experiment, which had no significant impact on the aromatic smell of the fermented feed ( Słupecka-Ziemilska et al, 2022 ; Uddin et al, 2023 ). Biagi et al (2007) reported that adding a small amount of butyric acid as a feed additive to the feed can improve the microbial intestinal flora of piglets and immune system.…”
Section: Discussionmentioning
confidence: 82%
“…However, butyric acid is easily oxidized and denatured, producing a pungent odor. A trace amount of butyric acid was produced after fermentation in this experiment, which had no significant impact on the aromatic smell of the fermented feed ( Słupecka-Ziemilska et al, 2022 ; Uddin et al, 2023 ). Biagi et al (2007) reported that adding a small amount of butyric acid as a feed additive to the feed can improve the microbial intestinal flora of piglets and immune system.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we also found the genus Intestinibacter to be associated with a lower risk of GH. There have been relatively few previous studies on Intestinibacter , but observational study and animal model have both reported the role of Intestinibacter in producing butyrate [ 24 , 25 ], which is a short chain fatty acid (SCFA) metabolized by GM. Placental inflammation and angiogenic factors played the central role in affecting blood pressure in pregnancy, and macrophages are the key regulator [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited previous studies have investigated the association between Intestinibacter and childhood obesity. However, both observational studies and animal models consistently emphasize the role of Intestinibacter in the production of butyrate, a metabolite generated through microbial fermentation ( 48 , 49 ). Butyrate increases fatty acid oxidation in the muscle and decreases lipolysis via the orphan G protein–coupled receptor 43 pathway in white adipose tissue ( 50 ).…”
Section: Discussionmentioning
confidence: 99%